Variables associated with malondialdehyde level in thalassemia major patients - Arum Gunarsih; Pustika Amalia; Imam Boediman (Paediatrica Indonesiana, 2012)
BackgmundThalassemia is the most cormnon hereditary haemolyticanaemia in the world, including in Indonesia. The main treatmentfor thalassemia is regular transfusions, but these are knO\vn to causeiron overload. Moreover, iron overload in jJô€®thalassemia patientsgenerates oxygen free radicals and peroxidative lipid injury. Ferritinserum concentration is used as indirect measurement of iron overload.Malondialdehyde (MDA), a terminal compound oflipid peroxidation,is used as an index of oxidative stress status.Objective To assess the correlation between iron overload (serumferritin level) and MDA as a marker of oxidative stress in thalassemiamajor patients.Methods This c rossô€®sectional study was conducted at CiptoMangunkusumo Hospital, Jakarta, from Mayô€®June 2009. Subjectswere thalassemia major patients (homozygous jJô€®thalassemia orjJô€®thalassemia;HbE) who received regular blood transfusions, ironô€®chelation, and vitamin E as an antioxidant. Data was collected by hisô€®toryô€®taking, physical examination, medical records, and questionnaires.Blocd specimens were dra\Vll from the thalassemia major subjects beforetransfusion and examined for serum ferritin and MDA levels.Results Fiftyô€®five subjects Mth thalassemia major (34 homozygousjJô€®thalassemia and 21 jJô€®thalassemia;HbE) were included in ourstudy. Mean serum ferritin level was 3693.2 (SD 21423),ug/L andme811 MDA level was 0.641 (SD 0.283) nmolimL. No cor relationwas found between serum ferritin and MDA levels in thalassemiamajor subjects (r=0.147, P=0.285). As additional results, this studyalso showed no correlation between MDA to reguler vitamin Econsumption (r=0.277, P=0.028) as well as MDA and nutritionalstatus (F0371, Pô€¯0.()J4).Conclusion There was no cor relation between serum ferritin leveland plasma MDA level in thalassemia major subjects, no cor relationsbetween MDA and regular vitamin E consumption, as well as MDAand nutritional status. [paediatr Indones. 2012;52:125,31].